1994
DOI: 10.1073/pnas.91.16.7628
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of apolipoprotein B-containing lipoproteins from HeLa cells is dependent on expression of the microsomal triglyceride transfer protein and is regulated by lipid availability.

Abstract: To Recent studies showing that a defect in the MTP is the proximal cause of abetalipoproteinemia indicate that this protein is required for assembly and secretion of apoBcontaining lipoproteins (10, 11). Abetalipoproteinemic patients have only trace amounts of plasma apoB-containing lipoproteins, resulting in extremely low TG and cholesterol levels (12). The cause of this phenotype is a defect in the pathway responsible for assembly and secretion of apoBcontaining lipoproteins since the apoB gene (13, 14) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
147
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(158 citation statements)
references
References 28 publications
9
147
1
Order By: Relevance
“…Previous studies have demonstrated that MTP is essential for the assembly of apoB-containing lipoproteins (12,13). Moreover, it has been shown that mutations in the MTP gene give rise to the phenotype of abetalipoproteinemia (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that MTP is essential for the assembly of apoB-containing lipoproteins (12,13). Moreover, it has been shown that mutations in the MTP gene give rise to the phenotype of abetalipoproteinemia (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that inactivate or abolish MTP give rise to the phenotype of abetalipoproteinemia, an almost total absence of apoB-containing lipoproteins in the plasma (10,11). Thus MTP is essential for the assembly and secretion of apoB-containing lipoproteins (12,13). Very recent results indicate that MTP is important for the early events in the assembly of endogenous rat apoB-48 VLDL.…”
mentioning
confidence: 99%
“…Inactivation of MTP in hepatic or intestinal cells invariably impairs apoB assembly and secretion (7,20,21). On the other hand, coexpression of the MTP 97-kDa subunit with recombinant apoB facilitates assembly of small, dense lipoproteins containing apoB in heterologous cells (22)(23)(24)(25). Although these studies have provided strong evidence that MTP is essential for apoB secretion as lipoproteins, our knowledge on the mechanism by which MTP facilitates VLDL assembly is incomplete and controversial.…”
mentioning
confidence: 92%
“…Initial transfection studies with non-hepatic cell lines (22)(23)(24)(25) suggested that the major function of MTP was to assist translocation of apoB across the membrane of ER. Since it was believed that the formation of primordial dense particles took place during apoB translocation, some researchers postulated that MTP activity was essential only in the early stage of apoB lipidation (26).…”
mentioning
confidence: 99%
“…43 Assuming that these effects occur in vivo, a reduced degradation of apo B caused by increased FFA, together with increased MTP activity, would accelerate the secretion of VLDL particles from the liver. 44,45 In 30-week-old OLETF rats, plasma triglyceride levels were over eightfold higher and plasma cholesterol levels 1.5-fold higher than in LETO rats of the same age. Insulin resistance and NIDDM are manifested at this stage.…”
Section: Figmentioning
confidence: 99%